Shifts in microbial food web structure and productivity after additions of naturally occurring dissolved organic matter: Results from large‐scale lacustrine mesocosms. (8th September 2015) - Sanders, Robert W.; Cooke, Sandra L.; Fischer, Janet M.; Fey, Samuel B.; Heinze, Adam W.; Jeffrey, Wade H.; Macaluso, Amy L.; Moeller, Robert E.; Morris, Donald P.; Neale, Patrick J.; Olson, Mark H.; Dean Pakulski, J.; et al.
Abstract: Predicting the effects of dissolved organic matter (DOM) on pelagic food webs can be difficult because DOM modifies water column optics and can have contrasting effects on species across trophic levels. We combined large mesocosm, smaller‐scale experiments and autoregressive modeling driven bu DOC concentration or DOM optical quality (colored DOM, or CDOM, measured as DOC‐specific absorbance at 320 nm, SUVA320 ) to assess how heterotrophic and phototrophic microbial populations were altered in a temperate oligotrophic lake. DOM additions yielded DOC concentrations of 1.6 mg L −1 (control) 2.5 mg L −1, 3.0 mg L −1, and 4.3 mg L −1 . Primary (PP) and bacterial (BP) production as well as heterotrophic and autotrophic protist abundances were stimulated in the higher DOM additions. BP responded rapidly to DOM additions, but unlike PP, returned to the level of controls within 2–7 d. A bioassay showed that the DOM was a nitrogen source for phytoplankton. The two models revealed that BP and edible phytoplankton were stimulated by CDOM (SUVA320 ), but only BP was stimulated by DOC concentration. Ultraviolet radiation (UV) inhibited protists in both models, but stimulated edible phytoplankton only in the SUVA320 model runs. These results suggest that in transparent oligotrophic lakes large influxes of terrestrial (high SUVA320 ) DOM will stimulate the microbial food web by providing a nutrient subsidy to bacteria and reducing exposure of protists to damaging UV. Nutrients associated with moderate DOM input may also stimulate PP relative to BP, as was observed in these and other experiments, rather than causing an overall system shift toward heterotrophy.